Effect of a Rapid Test Algorithm on Linkage to Medical Care and Viral Suppression Among New Jersey Residents, 2007 to 2015. Issue 7 (July 2018) - Mohammed, Debbie Y.; Davidow, Amy; Martin, Eugene; Ibrahim, Abdel; Paul, Sindy; Ryan, John; Bolden, Barbara
Abstract : Background: Efforts to identify and link human immunodeficiency virus-infected persons to medical care are the first steps to achieving viral suppression. In the United States, the goals are to link 85% of newly diagnosed persons to medical care in 30 days or less and for 80% to become virally suppressed by 2020. Among newly diagnosed residents from 2007 to 2015, in New Jersey, we evaluated the impact of a rapid testing algorithm (RTA) on linkage to medical care and viral suppression. Methods: This is a retrospective review of data from New Jersey's Enhanced HIV/AIDS Reporting System for residents, newly diagnosed at 13 years or older, from 2007 to 2015. We used survival analysis methods to estimate the proportion of residents and time to linkage to medical care and viral suppression. Results: Of 8508 newly diagnosed residents, 60.3% and 72.3% were linked to medical care in 30 days or less and 90 days or less, respectively; 45.7% achieved viral suppression in 365 days or less. Linkage to medical care in 90 days or less and viral suppression in 365 days or less were more likely among those tested by RTA than laboratory testing. The adjusted hazard ratios for linkage to medical care, in clinical sites were 1.41, (95% confidence interval [CI], 1.22–1.63 and 1.08, 95% CI, 0.97–1.2 in community sites. The adjusted hazard ratios for viral suppression in clinical sites were 1.25 (95% CI, 1.05–1.47 and 1.16, 95% CI, 1.01–1.32, in community sites. Conclusions: Implementation of a RTA may eliminate barriers to linkage to medical care and viral suppression leading to decreased morbidity, mortality, and transmission. Abstract : When compared with laboratory testing, New Jersey residents tested by rapid test algorithm, in both clinical and community sites, had shorter median times to linkage to medical care and viral suppression.Supplemental digital content is available in the text.